2020
DOI: 10.3390/jcm9082439
|View full text |Cite
|
Sign up to set email alerts
|

Core Outcome Measurement Instruments for Clinical Trials of Total Knee Arthroplasty: A Systematic Review

Abstract: (1) Background: We have updated knowledge of the psychometric qualities of patient-reported outcome measures and, for the first time, systematically reviewed and compared the psychometric qualities of physical tests for patients with knee osteoarthritis who are undergoing total knee arthroplasty. This work was conducted to facilitate the choice of the most appropriate instruments to use in studies and clinical practice. (2) Methods: A search of medical databases up to December 2019 identified the studies and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 99 publications
0
15
0
2
Order By: Relevance
“…Several studies concluded that the WOMAC and the Medical Outcomes Study Short-Form 36 (SF-36) could be recommended as primary measures in treatment studies [ 23 ]. A systemic review also showed that, overall, regarding patient-reported outcome measures, the KOOS, WOMAC, and SF-36 are the most comprehensively tested tools in this population and are worth considering [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several studies concluded that the WOMAC and the Medical Outcomes Study Short-Form 36 (SF-36) could be recommended as primary measures in treatment studies [ 23 ]. A systemic review also showed that, overall, regarding patient-reported outcome measures, the KOOS, WOMAC, and SF-36 are the most comprehensively tested tools in this population and are worth considering [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…PPTs are quantitative sensory tests that are widely used in the prediction and evaluation of clinical therapeutic effects in patients with KOA [ 40 43 ]. An experienced trained clinician (CXG) will perform all PPT measurements using the FDX-50 portable pain tester (Wagner Instruments, Greenwich, CT, USA) to minimize measurement variability.…”
Section: Methodsmentioning
confidence: 99%
“…PPTs are quantitative sensory tests that are widely used in the prediction and evaluation of clinical therapeutic effects in patients with KOA [40][41][42][43]. An experienced trained clinician (CXG) will perform all PPT measurements using the FDX-50 portable pain tester (Wagner Instruments, Greenwich, CT, USA) to minimize measurement variability.…”
Section: Primary Outcomementioning
confidence: 99%